PENGEMBANGAN MULTIMEDIA INTERAKTIF “PETOK PEJANDA” BERBASIS APLIKASI PREZI MATERI PERJUANGAN PARA TOKOH PEJUANG PENJAJAHAN BELANDA UNTUK KELAS 5 SDN PULOREJO - Pramita, Fransiska Dwi; Imron, Ilmawati Fahmi; Permana, Erwin Putera (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was motivated by the results of observations carried out at SDN Pulorejo. namely, the problem of low learning outcomes for grade 5 students in the social studies subject, history material, was found. The low student learning outcomes are caused by students not liking and considering social studies subjects, especially history, to be difficult and boring. Therefore, in this research, a trial was carried out to improve student learning outcomes by using the interactive multimedia "PETOK PEJANDA" based on the Prezi application. The aim of this research and development is to determine the validity, practicality and effectiveness of the interactive multimedia "PETOK PEJANDA" based on the Prezi application. This research uses the development research model and ADDIE method. This research obtained media and material validity results of 84%, the effectiveness of the media in limited trials obtained classical completeness of 90% while in extensive trials obtained classical completeness of 96%, and practicality in limited trials obtained a percentage of 94% and in extensive trials obtained percentage of 95%. Based on this percentage, it can be concluded that the interactive multimedia "PETOK PEJANDA" based on the Prezi application is valid, practical, and effective for use in grade 5 elementary school students.